Mapping of plant–fungal interactions on agriculture perception: a bibliometric analysis and systematic review - Asad, Suhail; Chen, Mei; Priyashantha, Alviti Kankanamalage Hasith; Gu, Peng; Liu, Jie; Shan, Zhiguo; Tibpromma, Saowaluck; Niu, Chen; Qadir, Masood; Akhtar, Muhammad; Kan, Xurundong; Xu, Yiren; et al. (Frontiers in Microbiology, 2025)
In nature, plants are always destined to interact with fungi. Thus, plant–fungal interactions are one of the unavoidable fields of study, particularly for agronomists. Fungi interact with plants in different lifestyles, pathogenic and symbiotic. Pathogenic relationships have adverse effects, causing devastating diseases in plants, while symbiotic interactions provide numerous benefits, promoting the growth and development of plants. The intricate relationship between fungi and plants has been the subject of extensive research, especially in the tropics, where there is a higher plant diversity and a strong positive correlation with fungi diversity. This extensive research has provided us with a wealth of knowledge about these interactions. In this study, we conducted a bibliometric analysis and systematic review, analyzing 733 research articles. A considerable growth was revealed in this field, particularly over the previous decade. Many studies during this period are concentrated in China, with a plethora of emerging researchers. More attention has been paid to genetic/molecular-based work over the last decade. In addition, researchers are promoting the use of plant–fungal interactions for sustainable agriculture, highlighting their crucial importance in mitigating crop stresses under both biotic (pests) and abiotic stresses, such as heavy metal pollutants, nutritional depletion, temperature rises, changes in water regimes, and elevated carbon dioxide concentrations. Considering future studies, further research is needed to elucidate the relationships between plants and fungi, particularly through multi-omics approaches. Network mapping and the influence of indigenous fungi on plant–fungal interactions are other, less-studied, important areas to focus on.